PENGABDIAN DAN PELATIHAN PENCAK SILAT DALAM MENINGKATKAN KEMAMPUAN ATLET - abdul rozak, lukman abdul aziz (Jurnal Muhammadiyah untuk Olahraga Indonesia, 2024)
This community service activity was carried out on June 29 2023 at 15.00-18.00 WIB at the Hall of FIKES 2 Muhammadiyah University of Pekajangan Pekalongan. Participants totaled 30 people. The participants were very enthusiastic about joining the pencak silat training. Before the practice was given, the participants were briefly given material about the latest 2022 competition techniques in addition to the basic techniques of pencak silat and also training in the components of basic pencak silat techniques. The method used is in the form of activities in this pencak silat sports training using a direct approach, demonstrations, discussions, practice and evaluation of training from athletes who participate directly on location, with theory and direct practice in the field. This training is provided so that participants know and understand about the latest pencak silat competitions, practice basic pencak silat techniques in improving techniques correctly, so as to encourage the creation of optimal pencak silat achievements. The material that I conveyed in this activity was regarding the basic techniques of the newest pencak silat in 2022 and basic technical practice training programs for supporting pencak silat athletes